A Microfoundation of Predator-Prey Dynamics - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2003)
Predator-prey relationships account for an important part of all interactions between species. In this paper we provide a microfoundation for such predator-prey relations in a food chain. Basic entities of our analysis are representative organisms of species modelled similar to economic households. With prices as indicators of scarcity, organisms are assumed to behave as if they maximize their net biomass subject to constraints which express the organisms risk of being preyed upon during predation. Like consumers, organisms face a budget constraint requiring their expenditure on prey biomass not to exceed their revenue from supplying own biomass. Short-run ecosystem equilibria are defined and derived. The net biomass acquired by the representative organism in the short term determines the positive or negative population growth. Moving short-run equilibria constitute the dynamics of the predator-prey relations that are characterized in numerical analysis. The population dynamics derived here turn out to differ significantly from those assumed in the standard Lotka-Volterra model.
Keywords: 330; organism; biomass; species; population; predator-prey dynamics